On Tesla-inspired Extended Quantum-Holographic Framework for Reprogramming Macro-Quantum Correlations of Individual and Collective Consciousness - Rakovic Dejan (Journal of Human Psychology, 2024)
Nikola Tesla's visions and inventions realized in his controlled altered states of consciousness were considered previously as manifestations of his meditative insights within an extended framework of quantum-holographic macroquantum correlations of individual & collective consciousness. This Tesla-inspired paper now focuses on related psychosomatic aspects of quantum entropy & entanglement, and consequences on the usually observable biological arrow of time & spiritual-informational time reversal. Finally we discuss spiritual-informational implications for free will and individual and collective consciousness reprogramming.
Keywords: Nikola Tesla